Updates in pelvic neuromodulation: the role of pelvic neuromodulation in pelvic disorders - Alsannan, Baydaa; Banakhar, Mai; Hassouna, Magdy (Frontiers in Urology, 2024)
Pelvic disorders affecting both male and female patients are major areas of concern for clinicians in cases where pharmacotherapy and behavioral therapy are not effective. In such cases, pelvic neuromodulation has become an alternative therapy that could relieve chronic pelvic pain and enhance the quality of life. The goal of this paper was to present a summary of the current therapeutic applications of various pelvic neuromodulation techniques and their efficacy in treating patients with a range of pelvic illnesses. Based on the available literature, this review assessed the validity and significance of the last 10 years’ advancements in the fields of sacral neuromodulation (SNM), posterior tibial nerve stimulation (PTNS), and pudendal neuromodulation (PNM), including meta-analyses, randomized controlled trials, and observational, prospective, and retrospective studies.